Evidence of Chinese herbal fumigation for knee osteoarthritis: A protocol for systematic review and meta-analysis. Issue 6 (12th February 2021) - Ou, Liang; Meng, Yingfu; Chen, Zehua; Zhang, Tiantian; Kong, Dezhong; Xu, Daoqing; Huang, Weichen
Abstract: Background: Knee osteoarthritis (KOA) is the most common cause of musculoskeletal pain and disability worldwide. Chinese herbal fumigation, an external therapy, is commonly used for the treatment of KOA, while there is no systematic review or meta-analysis designed to evaluate the effects of Chinese herbal fumigation on KOA. Methods: Seven databases including Cochrane Central Register of Controlled Trials, EMBASE, PubMed, China National Knowledge Infrastructure, Wanfang data, VIP, and Chinese Biomedical Literature Database will be searched up to October 31, 2020. Data that meet the inclusion criteria will be extracted and analyzed by using RevMan V.5.3 software. Two reviewers will assess quality of the included studies based on the Cochrane Collaboration risk of bias tool. The funnel plot and Begg test will be used to evaluate publication bias. And Grading of Recommendations Assessment, Development and Evaluation will be employed to assess the quality of evidence. Results: This study will provide high-quality evidence for Chinese herbal fumigation for the treatment of KOA in terms of effectiveness and safety. Conclusion: This systematic review will provide evidence to help us confirm the clinical efficacy of Chinese herbal fumigation in the treatment of KOA.